The Digital Enterprise: How to Reshape Your Business for a Connected World - Nicholas Carr (USA Harvard Business School Press, 2001)
With this bold collection of cutting-edge "Harvard Business Review" articles, the magazine's executive editor explores the fundamental changes that are happening in business as a result of the Internet, digital communications, and ubiquitous connectivity.
Keywords: Management; Data processing; Electronic commerce; Information technology; Business enterprises; Communication systems; Internet; Business Enterprises -- Communication Systems -- Management; Electronic Commerce -- Management; Information Technology -- Management; Internet; Management -- Data Processing